An Exploratory Research on Adaptability and Flexibility of a Serious Game in Operations and Supply Chain Management - Romagnoli, Giovanni; Galli, Matteo; Mezzogori, Davide; Zammori, Francesco (International Journal of Online and Biomedical Engineering (iJOE), 2022)
Serious games (SGs) in industrial engineering education are an established topic, whose implementations are continuously growing. In particular, they are recognized as effective tools to teach and learn subjects like Operations and Supply Chain Management. The research on SGs, however, is primarily focused on displaying applications and teaching results of particular games to achieve given purposes. In this paper, we provide an exploratory research on the flexibility and adaptability of a specific SG to different target groups and students’ needs in the field of operations and supply chain management. We first provide an overview of the SG and introduce its mechanics. Next, we explain how the mechanics has been implemented, by means of a set of parameters and indicators. We report the results of two different game sessions, played by a class of bachelor’s degree students at different levels of difficulty, which were achieved by altering some specific game parameters. By comparing the Key Performance Indicators (KPIs) in the two sessions, we report and discuss the consequences of the modified game parameters, in terms of impact on the difficulty level of the SG measured by the indicators. Experimental results match with our hypothesis, since the increased level of difficulty of sourcing and delivery times only deteriorates the related subset of indicators in the harder game session, without altering the remaining KPIs.